Mapping of Environmental Health Risks in Bonetambung Island, Makassar - A, Marwah; La Ane, Ruslan; Birawida, Agus Bintara; Azizah, R (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2017)
Bonetambung Island is one of small islands of Spermonde Island Group that had limited access to sea transportations and unavailable environmental sanitation facilities. This study aimed to map environmental health risks to identify the areas of environmental health hazard in Bonetambung Island, Makassar. This study was observational descriptive. Respondents in this study were all households in Bonetambung Island as many as 102 households taken by exchautive sampling method. The result showed that the environmental health hazards in Bonetambung Island were hazard related to the source of clean water (71,1%), domestic wastewater (71,2%) and the ownership of garbage (72,5%). Additionally, some unhealthy behaviors that provided an opportunity for exposure to hazards were not-washing-hand-with-soap behavior (54.2%), open defecation behavior (62.7%), not processing and managing household waste (96.1%), and not-treat-drinking-water behavior (25.5%). So that, the mapping of environmental health risks in Bonetambung Island were very high risk category located in RT 03, high risk category located in RT 02, and low risk category in RT 01.